Beyond the Lone Island: Leveraging Communities of Practice for Faculty Growth and Scholarly Success - Dr. Donna Zerr; Dr. Carissa Gober; David Wolff (The Advocate, 2026)
This article examines the transition from K–12 teaching to higher education faculty roles, emphasizing challenges related to isolation and scholarly expectations. Using Schlossberg’s (1981) Human Adaptation to Transition model, the authors reflect on moving from collaborative K–12 environments to a more solitary setting of higher education. Scholarly writing emerged as a challenge, often accompanied by imposter syndrome (Clance & Imes, 1978). Through participation in a university-sponsored writing camp, the authors discovered the benefits of collaborative scholarship and initiated a Community of Practice (CoP) within their department. This CoP fostered trust, accountability, and professional growth, reducing isolation and supporting faculty in achieving research goals. The authors learned the importance of structured collaboration and offer practical strategies for creating a CoP in higher education.
Keywords: Community of Practice (CoP); imposter syndrome; collaborative scholarship; K–12 to higher education transition